Handbook of megachurches - Hunt, Stephen, 1954- (Brill Handbooks on Contemporary Religion;, 2020)
"The growth of the megachurch (generally defined as a regular attendance of over 2,000 people) is undoubtedly one of the most exceptional religious trends of recent times, certainly within the Christian sphere. Spreading from the USA, megachurches have now become common globally - reaching different national and cultural contexts. The edited volume Handbook of Megachurches offers a comprehensive account of the subject from various academic perspectives: sociology, religious studies, religious history and religious studies among them. Topics covered include: the historical developments and growth, typologies, theology, popular culture, revivalism, social engagement, and the manifestation of megachurches in such countries as Canada, Russia, India and Africa. Contributors are: Richard Burgess, Mark Cartledge, Saliha Chattoo, Simon Coleman, Katie Corcoran, Andrew Davies, David Eagle, Stephen Hunt, Jonathan James, Torsten Löfstedt, Gordon Melton, Martyn Percy, Charity Rakestraw, Peter Schuurman, Kate Stockly, Azoneh Ukah, Marc von der Ruhr, James Wellman, Michael Wilkinson. Foreworded by David Bromley".